Development of a Total War Strategy to Face Cyber Threats in Aviation Systems: a Case Study of Asean Regional Strategic Environment and its Implications for Aviation Security - Anggreini, Monika; Priyanto, Priyanto; Sulistyanto, Sulistyanto; Hendra, Afrizal; Suryo, Almuchalif (Jurnal Indonesia Sosial Sains, 2025)
This research aims to analyze the implementation of aviation security in the face of cyber threats and formulate the best strategies to strengthen national digital defense in the perspective of the Universal War Strategy. The background of this research is driven by the increasing frequency and complexity of cyberattacks against global and regional aviation systems, which threaten aviation safety and national sovereignty. Based on data from the International Civil Aviation Organization (ICAO, 2023), cyberattacks in the aviation sector increased by 46% between 2020–2023, while the State Cyber and Cryptography Agency (BSSN, 2023) recorded more than 210 cyber incidents targeting Indonesia's air transportation system. This study uses a qualitative descriptive method, with two main theoretical foundations, namely George C. Edward III's policy implementation theory and Carl von Clausewitz's military strategy theory which is operationalized through SWOT-AHP analysis. The results of the study show that the implementation of cybersecurity policies in Indonesia's aviation sector still faces obstacles in terms of communication, resources, executive disposition, and bureaucratic structure. Factually, only 37% of national airport operators have cyber incident response teams (CSIRTs), while the digital security budget allocation is still below ICAO's recommendation of 2% of the total operational budget. A special finding from this study is the application of the concept of "Digital Universe War", which is the synergy of civilian, military, and technological forces in the national cyber defense system that is integrated with the ASEAN regional security ecosystem. Based on the SWOT-AHP results, the best priority strategy is the integration of national cybersecurity and aviation systems (weight 0.36), followed by increasing human resource capacity and strengthening regional cyber intelligence cooperation. This research contributes significantly to expanding the paradigm of universal warfare to the digital realm as a strategic instrument to maintain national aviation security and sovereignty in the cyber era.